An Adaptive Adjustment Mechanism for Carriage in ATTN Network - Yongju Xian; Huailiang Yi; Qili Zhang (Institute of Advanced Engineering and Science, 2016)
Internet based on TCP/IP is now faced with the problem of scalability, security, management and energy consumption, while the patch to Internet doesn’t solve the drawback of IP network essentially, which further intensifies the complexity of the network. In this paper, based on the research of ATTN network, an adaptive adjustment mechanism is proposed aiming at the problem of data retention and low resource utilization rate in the automatic configuration of the carriages. In which by the forecast of data retention and resource utilization, the carrier routes are dynamically adjusted. Finally, the scheme is further optimized, and tested on ATTN simulation platform, which shows the performance of ATTN network is improved.